Una cadena es tan fuerte como su eslabón más débil: El Déjä vu de la acreditación de las Instituciones Arbitrales - Velásquez De La Cruz, Ana Cristina (Pontificia Universidad Católica del Perú, 2025)
This article explores the evolution of the role of arbitral institutions within the Peruvian arbitration system with particular emphasis on the general framework of public procurement. We will examine—through a retrospective lens—how, from the enactment of Law No. 26850, the Public Procurement and Acquisitions Law published on August 3rd, 1997 to the current General Public Procurement Law, Law No. 32069, which came into effect on April 22nd, 2025, arbitral institutions have transitioned from being mere facilitators of arbitral proceedings—whose involvement depended on the parties’ will—to holding a leading role established by legislative mandate.

Este artículo desarrolla la evolución del rol de las instituciones arbitrales en el sistema arbitral peruano, con especial énfasis en el marco general de contrataciones públicas. Exploraremos, a través de una mirada al pasado, cómo es que a partir de la Ley 26850, Ley de Contrataciones y Adquisiciones del Estado publicada el 3 de agosto de 1997, hasta la actual Ley General de Contrataciones Públicas, Ley 32069 que entró en vigencia el 22 de abril de 2025, las instituciones arbitrales pasaron de ser un actor facilitador de la gestión arbitral, cuya presencia se sujetaba a la voluntad de las partes, a tener en la actualidad un rol protagónico por voluntad del legislador.
A chain is only as strong as its weakest link: The Déjà vu of the accreditation of arbitral institutions
Keywords: Public procurement; Arbitration institutions; Integrity; Arbitration; Efficient arbitration services; Contratación pública; Instituciones arbitrales; Integridad; Arbitraje; Servicios arbitrales eficientes; https://purl.org/pe-repo/ocde/ford#5.05.00